IMPLEMENTASI MEDIA PEMBELAJARAN TEBAK KATA DENGAN ISTILAH UNTUK MENUMBUKHAN KEAKTIFAN PESERTA DIDIK SEKOLAH MADRASAH ALIYAH - Khairul Umam; M Wartsil Widad; Yetti Hidayatillah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The background of this research is the absence of student participation in the implementation of the learning process, this is caused by a lack of student interest in learning which is motivated by the unprofessionalism of teachers in carrying out the learning process, starting from teachers who never use learning media, teachers who fierce towards students, even in a psychological approach this is very contrary to the provisions that are already in force. This research uses a qualitative descriptive research method. In the results of research carried out at PP. Nurul Karamah Babillah's demonstration of Sumenep's power shows that the application of learning media that should be implemented by all teachers in the school does not exist at all. The lack of teacher participation in providing learning media which should be a support in the learning process is actually very minimal.